2016
DOI: 10.1177/0009922815618487
|View full text |Cite
|
Sign up to set email alerts
|

Massachusetts Pediatricians’ Views Toward Body Mass Index Screening in Schools

Abstract: Objective Evaluate Massachusetts pediatricians' views toward school-based body mass index screening since its implementation. Methods Survey of 286 members of the Massachusetts Chapter of the American Academy of Pediatrics on attitudes toward screening and perceived impact on clinical practice. Results Overall, 36.3% supported screening, with suburban or rural pediatricians significantly less likely (vs urban) to indicate support. Less than 10% of pediatricians agreed or strongly agreed that screening improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Measuring student BMI at school is controversial, and numerous experts have raised concerns that school-based BMI screening may have unintended negative consequences . Massachusetts, which instituted BMI reporting in 2009, stopped sending BMI reports in 2014 because of concerns about stigmatization .…”
Section: Discussionmentioning
confidence: 99%
“…Measuring student BMI at school is controversial, and numerous experts have raised concerns that school-based BMI screening may have unintended negative consequences . Massachusetts, which instituted BMI reporting in 2009, stopped sending BMI reports in 2014 because of concerns about stigmatization .…”
Section: Discussionmentioning
confidence: 99%
“…36 Increasing evidence suggests that interventions to reduce obesity should focus on changing social, socioeconomic, and built environment factors, all of which play major roles in the development of obesity. 39,40 Measuring student BMI at school is controversial 41,42 and numerous experts have raised concerns that school-based BMI screening may have unintended negative consequences. 16,43,44 Massachusetts, which instituted BMI reporting in 2009, stopped sending BMI reports in 2014 due to concerns about stigmatization.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of such information, it is not possible to verify whether PFT places students at elevated risk for bullying in the school environment. Finally, 11% of 286 pediatricians surveyed in Massachusetts 79 reported that they had delivered counseling to parents about bullying related to school-based BMI screening. Given the very low response rate on this survey (18.6%) and the small number of pediatricians who mentioned bullying as an issue raised by parents in the clinical setting, this study provides only a weak indication that school-based PFT may be associated with bullying.…”
Section: Association Between Bullying and Physical Fitness Testingmentioning
confidence: 99%